THE EFFECT OF BIOGRAPHICAL CHARACTERISTICS AND CULTURAL DIVERSITY ON PERFORMANCE (Survey: Civil Servants of Lubuk Linggau Government) - ., Maulana (Journal of Management and Business, 2014)
This research was done in order to investigate the effect of Biographical Characteristics and Cultural Diversity on Performance in Civil Servants of Lubuk Linggau government. There were two variables in this research. The independent variables were Biographical Characteristics (X1)), Cultural Diversity (X2). The dependent variable was the performance of Civil Servants in Lubuk Linggau government. The objectives of this research were: a) to investigate the effect of Biographical Characteristics (X1), Cultural Diversity (X2) toward the performance of Civil Servants in Lubuk Linggau government, and b) to investigate which dominant independent variables affected the Performance of Civil Servants in Lubuk Linggau.government. The method used in this research was causal. The number of sample in this research was 100 Civil Servants in Lubuk Linggau government. The data were collected through questionnaire. Before the test of influence, the test on validity and reliability was conducted to see the level of validity and instrument trusted which can be used as a data collector. To Measure the relationship between variables, multiple regression analysis was used. Based on the analysis results, it was found that variables Biographical Characteristics (X1)), Cultural Diversity (X2) were altogether affected significantly on the Performance of Civil Servants in Lubuk Linggau government. The variation of dependent variables changes (performance) affected by independent variables were Biographical Characteristics (X1)), Cultural Diversity (X2) was 64.4 percent (R2 = 0.644) while the rest which was 35.6 percent was affected by other variables. It means that if the changes were done together, it would affect the Performance of Civil Servants in Lubuk Linggau government which was 64.4 percent. The Result in this research, the independent variables of Biographical Characteristics (X1), Cultural Diversity (X2) partially and simultaneously affected the Performance of Civil Servants in Lubuk Linggau City government.